The Iraq War and democratic politics - Danchev, Alex.; MacMillan, John, 1963- (London ; New York : Routledge, 2005)
This book examines the meaning of the 2003 Iraq war for democratic politics.
The Iraq War and democratic politics / John MacMillan -- The global setting : US foreign policy and the future of the Middle East / Richard Falk -- Bush's war : the Iraq conflict and American democracy / John Dumbrell -- The neo-cons : neo-conservative thinking since the onset of the Iraq War / Dan Plesch -- The United Kingdom / Dan Keohane -- The European dimension / John Vogler -- Turkey : democratic legitimacy / Christopher Brewin -- 'It seemed the best thing to be up and go' : on the legal case for invading Iraq / Patrick Thornberry -- The transition to democracy in Iraq : historical legacies / Gareth Stansfield -- The Democratic transition in Iraq and the discovery of its limitations / Glen Rangwala -- Iraq : political reconstruction and liberal theory / John Horton and Yoke-Lian Lee -- Afghanistan and Iraq : failed states or democracy on hold? / Iftikhar H. Malik -- The Iraq body Count Project : civil society and democratic deficit / John Sloboda -- Story development, or, Walter Mitty the Undefeated / Alex Danchev.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Iraq War, 2003-2011 -- Moral and ethical aspects; United States -- Politics and government -- 2001-2009.; United States -- Foreign relations -- 2001-2009.; Democracy -- Iraq; World politics -- 1989-; Guerre en Irak, 2003-2011 -- Aspect moral; États-Unis -- Politique et gouvernement -- 2001-2009.; États-Unis -- Relations extérieures -- 2001-2009.; Politique mondiale -- 1989-; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Democracy; Ethics; Diplomatic relations; Politics and government; World politics; Iraq; United States; Buitenlandse politiek; Democratie; Internationale veiligheid; Golfoorlog (2003); Legitimiteit; Since 1989